Analisis Efisiensi Perbandingan Penggunaan Transportasi Laut Dan Transportasi Udara Dalam Pengiriman Barang Antar Provinsi - Fadhlan Rizky Sawa Madani; Siti Sahara (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This research aims to conduct an efficiency analysis of the use of sea transportation and air transportation in sending goods between provinces. Transportation of goods between provinces has an important role in supporting the distribution and economy of a region. In this context, the research focus is aimed at two main modes of transportation, namely sea transportation and air transportation. The efficiency analysis method includes collecting data related to the cost, time and efficiency of sending goods using these two types of transportation. Next, the data is analyzed to identify the advantages and disadvantages of each mode of transportation, as well as spreading its impact on the efficiency of sending goods from one city or province to another to meet needs in each destination province. This research uses quantitative methods